If it's not what You are looking for type in the equation solver your own equation and let us solve it.
+2y-8=3(y-11)
We move all terms to the left:
+2y-8-(3(y-11))=0
We calculate terms in parentheses: -(3(y-11)), so:We get rid of parentheses
3(y-11)
We multiply parentheses
3y-33
Back to the equation:
-(3y-33)
2y-3y+33-8=0
We add all the numbers together, and all the variables
-1y+25=0
We move all terms containing y to the left, all other terms to the right
-y=-25
y=-25/-1
y=+25
| 200=1.5x | | X+2x+1+2x+3=29 | | (m-2)=-2(-2m+6) | | (3+4x)=16 | | x/2+x=3 | | (m-2)=-2(-2m+6 | | 3(x5)=2(x+5) | | X2+4x=20 | | 3(x5)=2(x+50 | | 14+1/3x=180 | | 7/4w-1=20 | | 9x-(2x+8)=20 | | 0,05x+0.10(200-x)=0.45x | | -3/2=-3/7w-2/3 | | 30x+5x^2=3600 | | 2x(x+3)-(x^2-9)=0 | | x+2x+3x=5.5 | | √2x+10=√x+3 | | 7x-2x9=5x-6 | | 3x(x+3)-(x^2-9)=0 | | y^-1/2=7 | | 5x+24=5(x-1/2) | | x^2=-(64/9)+8x | | 2*x-10=x+3 | | +12-3D=5d+6 | | x^2=(64/9)-8x | | 3(x-5)=3x-5=35 | | x^2=64/9-8x | | 14x-7=5+21x | | 3x^2+14x-60=0 | | -18=-5-k-13 | | 2x-2/6x-2=0 |